Implementasi Teknologi Restful Web Service Dalam Pengembangan Sistem Informasi Perekaman Prestasi Mahasiswa Berbasis Website (Studi Kasus: Fakultas Teknologi Pertanian Universitas Brawijaya) - Wiku Galindra Wardhana; Issa Arwani; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Besides being demanded by experts in the academic field, students are also required to have achievements. The Faculty of Agricultural Technology Brawijaya University seeks to to give recognition of the achievements of its students by recording student achievements. However, the recording of these achievements can not be done optimally because it is still done manually. Therefore, an information system that can record student achievement at the Faculty of Agricultural Technology is needed with the aim to facilitate the collection of student achievement data. This system was developed on a website platform with RESTFUL web service technology. System development is done by prototyping method that starts from the requirement analysis. Next, a prototype system was made and an evaluated by the head of the information system planning and public relation Faculty of Agriculture Technology. From the evaluation results were carried out repairs and re-prototype presentations until the prototype was approved. The results of the requirement analysis are illustrated by use case diagram, use case scenario, and activity diagram. The system design are illustrated by sequence diagram, class diagram, and physical data model. The website implementation uses the Laravel framework and the REST API implementation uses the Lumen framework. Then the system is tested using blackbox testing with a percentage of test results is 100% which indicates the system complies with specifications. In addition, usability testing was done using the System Usability Scale with a value of 78. Based on the values obtained, the system categorized on Good category with C on value scale and the acceptability range is on Acceptable category.